PENGARUH METODE ADAPTIVE LEARNING BERBASIS ANDROID TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN SENIBUDAYA SISWA KELAS VIII DI SMPN 4 TAMALATEA - Rahmat HR; Irmawati Thahir; Kasman, Kasman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This thesis is entitled "The influence of the Android-based Adaptive Learning method on the learning outcomes of students in arts and culture subjects in class VIII SMPN 4 Tamalatea." The aim of this research is to determine the influence of the Android-based Adaptive Learning method on the learning outcomes of students in arts and culture subjects in class VIII SMPN 4 Tamalatea. This research uses quantitative methods. Data collection techniques in this research use observation, test sheets and documentation. Determination of the sample size based on the Krejcie and Morgan table was 56 students. Based on the research results, the t test results with the help of the SPSS 25 software program produced a sig value of 0.010. Which means that the significance value is less than 0.5  is rejected and  is accepted, it can be concluded that the use of the Android-based Adaptive Learning method has an effect on student learning outcomes in class VIII Arts and Culture at SMPN 4 Tamalatea.